PENGARUH FASILITAS, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA GOLDVITEL HOTEL SURABAYA - Natasya, Chika; Rosyadi, Jessica Angelia; Deograsias, Juliani Stefani; Ferdinand, Yoseph Yustinianus (UNIKA Santo Thomas, 2024)
This Research is made to proof and analyse the effect of Facilities, Quality of Service, and Price on Customer Satisfaction at Goldvitel Hotel located at Jl. Basuki Rahmat No.147, Surabaya. In this researchers in this research uses quantitative approach with sample taken using Nonprobability Sampling with purposive sampling type and using a 0 liker scale questionnaire. The data analysis technique used is multiple linear regression analysis using the SPSS 26 application. There are 75 Respondents the results shows that Price (X2), and Quality of Service (X3) has a significant and positive correlation on Customers Satisfaction. Meanwhile, Facility (X1) has not a significant and negative correlation on Customer Satisfaction. This significant and negative association is likely caused by customer’s tendency to ignore the facility provided if the price offered is low enough